(untitled) (Research, Society and Development, 2021)
Self-esteem is the way an individual knows himself and how he relates to his own body. The physical image of an individual is a mental representation according to their perspective, not restricted to sensations and thoughts, but to the aspect of their own body. This study aimed to evaluate the benefits of aesthetic procedures in improving self-esteem. This is a literature review. Searches were performed through electronic databases online scientific electronic libraries - Scielo, Bireme and Google academic institutions and LILACS (Scientific and Technological Literature of Latin America and the Caribbean / VHL-Virtual Health Library, through the descriptors self-esteem, self-image and aesthetic procedures The analysis of the results described the positive impacts on the individual’s self-esteem. It was concluded that aesthetic procedures help to raise self-esteem, transforming a positive self-concept and being able to see its beauty and qualities. about the topic.